OS MATERIAIS MANIPULÁVEIS E OS JOGOS PEDAGÓGICOS COMO FACILITADORES DO PROCESSO DE ENSINO E APRENDIZAGEM DAS OPERAÇÕES COM NÚMEROS INTEIROS - Bordin, Laura Moreira (2011)
This paper aims at analysing how educational games and manipulative materials contribute to the comprehension of addition, subtraction, multiplication and division operations as well as to the exponentiation of intager numbers. 57 seventh-grade students from a public elementary school of Santa Maria, RS participated in this research. The research followed a qualitative approach, in which the teacher acted as the researcher; thus, experiencing the relations between the students themselves and between the students and the research tools. Data analysis took into consideration the field journal of the teacher and the reports of the 28 students who constitute one of the groups investigated. The introduction to the operations has happened by means of manipulative materials, composed by green small squares, which represent the positive numbers, and orange small squares, which represent the negative numbers. In order to systematize and evaluate the learning process, one has taken into consideration educational games, which were created on the basis of pre-existing games. The results show that the main objective of this research has been achieved, since the participants demonstrated effort and commitment into games. Besides, the evaluation tests revealed that learning has really improved. The students who participated in this research understood all the Math operations without having to memorize rules; rather, they were able to understand them by means of interaction and manipulation of tools that helped them in the conceptualization of such a content, which has been considered one of the most complex by seventh-grade students in the study of Math at Elementary School.